Teknik Retorika dalam Pidato Joko Widodo Di Youtube - Sari, Yunita; Supriyadi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
This research is entitled rhetoric techniques in Joko Widodo’speech on Youtube. The reason why the writer is writer is interested in choosing the title of this research is because Joko Widodo always makes speeches with sentences that are easy to understand and understand as well as practical speech content with a relaxed speech style that is easily digested by listeners research problems: (1) How is the rhetorical technique of Joko Widodo’s pathos form in a speech on Youtube? (2) How is the rhetorical technique of Joko Widodo’s logos in a speech on Youtube? Joko Widodo in a speech on Youtube aims to describe, analyze, interpret and conclude the pathos and logos techniques of Joko Widodo in a speech on Youtube. This research includes qualitative method. The source of this research data is Joko Widodo in a speech downloaded from Youtube in January 2020. This study uses the theory proposed by Suhandang (2009), Keraf (2006), and Abidin (2013). This research uses documentation technique. The results of research on Joko Widodo’s rhetorical technique in speeches on Youtube found that there were 15 techniques, including (1) pathos in the form of hope 5 data, hatred 2 data. Affection 2 data. Emotion 1 data (2) logos in the form of enthusiasm 5 data used Joko Widodo. So it can be concluded that the rhetorical technique used by Joko Widodo is more dominant using the pathos rhetoric technique in the form of hopes to influence the listener to be enthusiastic about carrying out activities, especially in achieving life goals, while the logos rhetoric technique as a whole uses an entiment strategy. Entiment strategy is used to form a logic or frame of mind.